Croconato-bridged copper(ii) complexes: synthesis, structure and magnetic characterization. (24th April 2017) - Massoud, Salah S.; Williams, Gabrielle F.; Louka, Febee R.; Henary, Maher M.; Herchel, Radovan; Trávníček, Zdeněk; Fischer, Roland C.; Mautner, Franz A.
Abstract : Three croconato-bridged Cu(ii ) complexes were synthesized and structurally and magnetically characterized. Abstract : Three croconato-bridged Cu(ii ) complexes were synthesized and structurally characterized including dinuclear [Cu2 (Et4 dien)2 (μ1, 2, 3, 4 -C5 O5 )](ClO4 )2 ·3H2 O (1 ) and [Cu2 (pmap)2 (μ1, 2, 3, 4 -C5 O5 )](ClO4 )2 ·2H2 O (2 ) and the 1D coordination polymer {[Cu(dmpzp)(μ1, 2, 3, 4 -C5 O5 )]·H2 O} n (3 ), where Et4 dien = N, N ′, N ′′, N ′′-tetraethylethylenetriamine, pmap = bis(2-(2-pyridyl)ethyl)-(2-pyridylmethyl)amine and dmpzp = 1-(2-methylpyridyl)-3, 5-dimethyl-1- H -pyrazole. The synthesized complexes were further characterized by a single crystal X-ray analysis which revealed the bis-bidentate chelating nature of the μ1, 2, 3, 4 -croconato ligand with the intra-dimer Cu⋯Cu bond distances ranging from 6.79 to 7.69 Å across the bridged croconate. The magnetic susceptibility measurements at varying temperatures (1.9–300 K) showed that the complexes exhibit a weak antiferromagnetic (AF) coupling with J values = −2.67 cm −1 for1 and2, and −4.05 cm −1 for3 . The weak AF coupling was also predicted based on the DFT calculations. The magnetic properties of the complexes are discussed in light of their structures and compared with the previously reported croconato-bridged Cu(ii ) complexes.